2022
DOI: 10.1039/d2dt01127a
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of halogenated tin phosphinoyldithioformate complexes against several cancer cell lines

Abstract: Organotin complexes are studied as promising alternatives to the anticancer drug cisplatin. We report two monoorganotin(IV) complexes based on a dibenzyl phosphinoyldithioformate (H-DBPTF) ligand, containing either bromide (Sn-DBPTF-1) or chloride...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…Conversely, a very low percentage of cells were in the S phase. Similar findings were reported by other authors, who demonstrated that halogenated tin phosphinoyldithioformate complex-derived compounds induced the inhibition of proliferation but not accumulation in the S phase of the cell cycle [32]. Furthermore, the anticancer activity of di-and triorganotin(IV) compounds associated with D-(+)-galacturonic acid was reported to be associated with a block in the G0/G1 phase [20].…”
Section: Discussionsupporting
confidence: 88%
“…Conversely, a very low percentage of cells were in the S phase. Similar findings were reported by other authors, who demonstrated that halogenated tin phosphinoyldithioformate complex-derived compounds induced the inhibition of proliferation but not accumulation in the S phase of the cell cycle [32]. Furthermore, the anticancer activity of di-and triorganotin(IV) compounds associated with D-(+)-galacturonic acid was reported to be associated with a block in the G0/G1 phase [20].…”
Section: Discussionsupporting
confidence: 88%
“…Chromium has been shown to increase the risk of PCA, 42 but additional evidence is needed to support this finding. The organotin complex is cytotoxic to PCA, 146 but its specific mechanism remains to be further studied. HIF‐1α counteracts the aggressiveness of PCA induced by hyperglycemia, and the concentration of HIF‐1α is positively correlated with the concentration of CoCl 2 , which may reduce the aggressiveness of PCA by increasing the expression of HIF‐1α 147 .…”
Section: Other Trace Elementsmentioning
confidence: 99%
“…[15][16][17] Meanwhile, their anticancer activities have also been initially investigated, showing that some of these compounds have significant antiproliferative activity against tumors, even higher than cisplatin. [14,18,19] For example, two bis(tricyclohexyltin)benzenedioxyacetates with the tetrahedral structure were found to be highly cytotoxic to MCF-7, COLO205 (colon carcinoma), and HeLa cells than cisplatin, up to 66-fold. [20,21] More importantly, these two compounds showed stronger antiproliferative activity against HeLa cells compared with MCF-7 and COLO205.…”
Section: Introductionmentioning
confidence: 99%